Sayyid Abul Anlo Mawdodo's views on Ijtihod and their relevance to the contemporary Muslim society - Haque, Munawar (2010)
The purpose of this article is to explore the views of Sayyid Abul AÑlÉ MawdËdÊ on ijtihÉd. It intends to trace the origins of MawdËdÊ’s ideas within the social, cultural and political context of his time, especially the increasing influence of modernity in the Muslim world. The study shows that MawdËdÊ’s understanding of ijtihÉd and its scope demonstrates originality. For MawdËdÊ, ijtihÉd is the concept, the process, as well as the mechanism by which the SharÊÑah, as elaborated in the Qur’Én and the Sunnah is to be interpreted, developed and kept alive in line with the intellectual, political, economic, legal, technological and moral development of society. The notion of ijtihÉd adopted by MawdËdÊ transcends the confines of Fiqh (jurisprudence) and tends therefore to unleash the dormant faculties of the Muslim mind to excel in all segments of life.